Eye tracking directionality - Pavlović, Nataša (Array, 2009)
The paper reports on a study investigating directionality in translation processes by means of eye tracking. The following hypotheses are tested: 1. In both directions of translation, processing the TT requires more cognitive effort than processing the ST ; 2. L2 translation tasks on the whole require more cognitive effort than L1 tasks ; 3. Cognitive effort invested in the processing of the ST is higher in L1 translation than in L2 translation ; 4. Cognitive effort invested in the processing of the TT is higher in L2 translation than in L1 translation ; 5. In both directions, students invest more cognitive effort in translation tasks than do professionals. The hypotheses are tested through a series of experiments involving student and professional subjects who translate two comparable texts, one into their L1 (Danish) and the other into their L2 (English). The following data from the translation tasks are analyzed: gaze time, average fixation duration, total task length and pupil dilation, all of which are assumed to be indicative of cognitive effort. Only Hypothesis 1 is found to be wholly confirmed by our data ; the remaining hypotheses are only partially confirmed, that is, confirmed by some indicators and not by others, or confirmed for only one group of subjects.